Etnogeografia Macuxi: o lugar na memória da Comunidade Indígena Raposa 1, Estado de Roraima - Santos, Éder Rodrigues dos (Universidade Federal de Roraima, 2022)
The study aims to understand the socio-spatial dynamics and topophilia of the Macuxi families of the Raposa indigenous community, Raposa Serra do Sol Indigenous Land (TIRSS), municipality of Normandia (RR). Until the beginning of the 20th century, the population of this community resided in the mountains, located on the borders of Brazil and Guyana, and descended to occupy the plowing, constituting the indigenous community of Raposa 1. In this sense, the research uses ethnography to describe the socioterritorial relations, having existential phenomenology as a theoretical framework, applies human geography to analyze the representations of space in the collective imagination. Through fieldwork it was possible to produce and gather maps of the community's equipment and services, in addition to mental maps built from community members. Some narratives in the mother tongue have been translated into Portuguese. The mobility of families occurred, possibly, due to the interventions of non-Indian culture in the last century, added to the natural conditions favorable to life in the fields. The mountains of the Raposa region constitute in the collective memory of the Macuxi people, sacred and affectionate spaces, immanent to the Amerindian way of life, in the corporeal, emotional and spiritual relationship of the human and non-humans with the place.